Comparative Study of Soil Radon Concentration Levels Using Active and Passive Detectors - N. M. Ershaidat; B. A. Al-Bataina; W. S. Al-Rayashi (Jordan Journal of Physics, 2025)
Passive radon diffusion dosimeters containing CR-39 detectors, and an active electronic device, RAD7® , were used for measuring soil radon concentration levels, at different depths, in a phosphatic site in the city of Irbid, north of Jordan. Time-averaged values of the active detector readings based on the periodicity of soil radon concentration levels are compared with measurements of the passive detectors at different depths. An acceptable agreement is observed. Highlights  Soil radon measured using an active detector (RAD7® ) and a passive one (CR-39).  Diurnal periodicity of soil radon diffusion and time-averaged values of RAD7® readings.  The “average” readings of the RAD7® are compared to the measurements of the CR-39. Keywords: Soil; Radon; Active detector, RAD7® , CR-39 dosimeters; Phosphate